2003
DOI: 10.1007/s00268-003-6907-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Management of Bile Leakage after Hepatic Resection

Abstract: The aim of this study was to identify the perioperative risk factors for postoperative bile leakage after hepatic resection and to propose a treatment strategy for such leakage when it does occur. Between 1992 and 2000 a total of 313 hepatic resections without choledocojejunal anastomosis were performed at our institute. Risk factors related to bile leakage were identified with univariate analysis, and strategies were evaluated in relation to the findings of postoperative fistulography. Postoperative bile leak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
205
3
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(226 citation statements)
references
References 17 publications
10
205
3
8
Order By: Relevance
“…In the study of Yamashita et al [3], biliary leakage had occurred in 4% of patients. Nagano et al [11] reported biliary leakage in 5.4%. Other studies showed biliary leakage in 5.8% [12], 7.2% [13] and 8.1% [14] of patients.…”
Section: Incidence and Risk Factors Of Biliary Leakagementioning
confidence: 99%
“…In the study of Yamashita et al [3], biliary leakage had occurred in 4% of patients. Nagano et al [11] reported biliary leakage in 5.4%. Other studies showed biliary leakage in 5.8% [12], 7.2% [13] and 8.1% [14] of patients.…”
Section: Incidence and Risk Factors Of Biliary Leakagementioning
confidence: 99%
“…Due to improvements in liver surgery, postoperative mortality and morbidity decreased dramatically over the last decades [1][2][3]. However, operations are still not hazard-free [1].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of bile fistula after liver surgery at the resection site has been reported to be 5–21% [32,33,34], while the definition of a bile fistula may differ from ‘a continuous drainage for more than 2 days with a bilirubin level over 20 mg/dl or 1,500 mg/day’ to ‘drainage of bile from abdominal wound or drain with a bilirubin level of more than 5 mg/dl’. Risk factors for leakage after liver surgery include resection surface area >60 cm 2 , exposure of major Glisson’s sheath, S4 resection, intraoperative blood loss and preoperative chemoembolization [32, 34]. In preventing this bile leakage, peroperative treatment of the remnant liver is extremely important and infrared coagulation, argon beamer, fibrin glue or hemostatic collagen fleeces might be helpful, but meticulous preparation during resection remains the most important factor with adequate placement of clips and sutures.…”
Section: Clinical Applicationsmentioning
confidence: 99%